A Survey of social support and psychosocial compliance in patients with breast cancer - Gülsüm Nihal Çürük; Pınar Tekinsoy Kartin; Arzu Şentürk (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Objective: The aim of the study was to investigate social support and psychosocial compliance in patients with breast cancer. Methods: The research was carried out on 131 patients diagnosed with breast cancer. The forms containing patients' demographic information were prepared by the researcher and Multidimensional Scale of Perceived Social Support (MSPSS) and Psychosocial Adjustment of Illnes Scale-Self Report Scale (PAIS-SR) were used as the data tools. Data were collected during personal interviews with patients, and were evaluated on computer using SPSS packet program. Mean, standard deviation, t-test and Mann-Whitney U-Test, one way variance, Kruskal Wallis test Kolmogorov-Simirnov test, Spearman correlation analysis were used in the statistical analysis.  Results: The mean score of MSPSS was 60.9±8.2 and the mean score of PAIS-SR scale was 56.0±9.5. It was found out that level of psychosocial adjustment of 3.8% of the patients was "good", level of psychosocial adjustment of 22.2% of them was "fair" and level of psychosocial adjustment of 74.0% of them was "poor". It was found that there was a negative and significant correlations between MSPSS and PAIS-SR. Conclusions: Perceived social support levels of breast cancers patients were found to be above the average and perceived of psychosocial adjustment were found to be below the average. It was concluded that social support for patients with breast cancer had an influence on their psychosocial adjustment to illness.